Evaluation of the E-Government Policy for the Civil Service Information System (Siap) in the Bekasi City Government Environment - Rizkanti Cahya Indah Utami; Lina Miftahul Jannah (Economic: Journal Economic and Business, 2025)
The quality of public services in Indonesia is currently under scrutiny. Bureaucracy in Indonesia is associated with a negative stigma that undermines public trust. This study aims to evaluate the implementation of e-government policies in personnel management through the Apparatus Information System (SIAP) in the Bekasi City Government (Pemkot) using the CIPP (Context, Input, Process, Product) model. SIAP Bekasi City currently has quite good achievements at the city and national levels. An obstacle in this study was the decline in the Public Satisfaction Survey (SKM) score of the Bekasi City Government from 2020 to 2023, based on 2023 data of 83.65. Qualitative data collection techniques were used in this study. The findings of this study indicate that SIAP Bekasi City is still not optimal in fulfilling the product element in personnel data management in the Bekasi City Government. The recommendation of this study is to maximize the evaluation results as material for further discussion to improve service quality.